The Association between Triglycerides and Glucose (TyG) Index and Parameters of Metabolic Syndrome - SN, Sigit Anugerah Putra SN; Dharma Lindarto (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Background: The triglyceride and glucose index (TyG index) has become an attractive option due to the highly available and inexpensive biochemical markers for diagnostic of insulin reciatance (IR). The aim of this study was to investigate the association between TyG index and parameters of metabolic syndrome patients. Method: A cross-sectional was conducted in outpatient polyclinics of the Endocrine-Metabolic division of RSUP H Adam Malik Medan. Criteria of Metabolic Syndrome: (i) abdominal obesity: waist circumference of ≥80 cm in women and ≥90 cm in men in Asean, measured at the umbilical level in a standing position; (ii) systolic blood pressure (SBP) of ≥130 mmHg or diastolic blood pressure (DBP) of ≥85 mmHg (or treatment with an antihypertensive medication), measured in all subjects using a validated digital electronic tensiometer in both upper limbs in a seated position after 15 minutes of rest; (iii) triglycerides levels (TG) of ≥150 mg/dL (1.7 mmol/L) or statin/fibrate treatment; HDL-cholesterol levels (HDL-C) of >80 cm in women and >90 cm in men). Result: In this study there were 20 metabolic syndrome patients. From the data, all patients are obese and HbA1c is normal. There is a significant relationship between TyG and HDL-C and TG (r=-0.60; p=0.005** and r=0.88, p= 0.001**, respectively). Conclusion: There is a significant relationship between TyG and HDL-C and TG of metabolic syndrome patients. Keywords: TyG, Metabolic Syndrome Parameters